Advances in innate immune memory of macrophages - Safir Ullah Khan; Munir Ullah Khan (Exploration of Immunology, 2022)
Immunity is usually classified into two categories: innate immunity and adaptive immunity, distinguished by the process and characteristics of the immunological impact. It was widely assumed that only adaptive immunity possessed memory features; however, current research has revealed that innate immunity, like adaptive immunity, possesses memory properties as well. “Trained immunity”, also known as “innate immune memory”, is a phenomenon that occurs when the immune system’s innate cells are stimulated and then undergo epigenetic reprogramming and metabolic alterations. When it comes to innate immunity, macrophages are essential since they have immunological memory capabilities and play a significant role in the body’s immunity. The concept of innate immune memory expands the definition of immunological memory and offers a broader view of immune response research. This article reviews the properties, mechanism, and significance of macrophage innate immune memory in disease.